Forensic Case Formulation: Exploring the Knowledge, Opinions, and Training Experiences of Staff Working Within the Offender Personality Disorder Pathway - Wheable, Victoria (International journal of offender therapy and comparative criminology, 2026)
Forensic case formulation (FCF) is a key activity within the Offender Personality Disorder Pathway (OPDP), performed by OPDP specialist offender managers (OMs) and psychologists. Although FCF training is provided to OMs, there are a number of questions about the adequacy and effectiveness of this training. Furthermore, it is unclear whether psychologists receive sufficient support to keep their FCF skills relevant and effective over time. This study aimed to investigate the FCF training experiences of OPDP staff, to assess staff satisfaction with this training, to identify ways of improving this training, and to explore the value of FCF from a staff perspective. To meet these aims, OPDP staff were asked to complete an online Qualtrics survey disseminated nationally. Results reveal a lack of standardized FCF training across the OPDP, contributing to poor staff satisfaction and confidence. These results highlight a need for FCF training improvement within the OPDP.